ANALISIS PERAMALAN AGRIBISNIS PANGAN DI KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Rahmanta, Rahmanta; Siti Khadijah Hidayati Nasution; Edi Warsito (Fakultas Pertanian Universitas Janabadra, 2025)
North Sumatra Province is one of the food crop production centers in Indonesia, including Simalungun Regency. Fluctuations in food crop production from year to year experience ups and downs making food production forecasting quite important. This research aims to analyze food production forecasting, namely rice, corn, and cassava in 2023-2033 using the Eviews 13 software application. The research method used is the ARIMA method, then the best ARIMA method is used for forecasting food production in Simalungun Regency in the future. The data used in this research is secondary data from 1996 to 2022 obtained from the Central Bureau of Statistics and the Food Crops and Horticulture Office. The results showed that Simalungun Regency in 2023-2033 experienced an increase in rice and cassava production, while corn experienced a decrease.